1964
DOI: 10.1099/00221287-37-2-209
|View full text |Cite
|
Sign up to set email alerts
|

The Metabolism of Escherichia coli and other Bacteria by Entodinium caudatum

Abstract: SUMMARY14C-labelled Escherichia coli and other bacteria were used to measure their uptake by washed suspensions of Entodinium caudatum. All the bacteria tested were engulfed by the protozoa with a maximum uptake of 1.1 x 104 E. colilprotozoon a t an initial rate of over 200 bacterialprotozoonl min. After 30 min. only 12 % of the engulfed bacteria were still viable. 50 yo of the bacterial carbon was retained by the protozoa and, after breakage of the protozoa and centrifugation of the homogenate, 40% of this ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
52
3
1

Year Published

1968
1968
2013
2013

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 94 publications
(59 citation statements)
references
References 9 publications
3
52
3
1
Order By: Relevance
“…The presence of entodinia decreases the average number of bacteria and also markedly decreases the peak concentration. Coleman (1964) found that Entodinium caudatum, in vitro, could ingest 12,000 Escherichia coli per protozoan per hr. If the rate of uptake of bacteria by the number of E. caudatum present in sheep 28 (Entodinium), which is about 25 x 1oS per ml., were of this same order, then it could be calculated that the protozoa could when most active almost completely nullify the increase in rumen bacterial population due to division of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The presence of entodinia decreases the average number of bacteria and also markedly decreases the peak concentration. Coleman (1964) found that Entodinium caudatum, in vitro, could ingest 12,000 Escherichia coli per protozoan per hr. If the rate of uptake of bacteria by the number of E. caudatum present in sheep 28 (Entodinium), which is about 25 x 1oS per ml., were of this same order, then it could be calculated that the protozoa could when most active almost completely nullify the increase in rumen bacterial population due to division of the bacteria.…”
Section: Discussionmentioning
confidence: 99%
“…The generally more frequent appearance of the other Gram-negative rods may be a reflexion of better rumen conditions for growth, although it is difficult to say what these conditions are. Coleman (1964) found that when Entodinium caudatum ingested Escherichia coli labelled with 14C amino acids, the amino acids were incorporated into protozoal protein after digestion of the bacteria, and also that some of the hydrolysed bacterial protein was 'washed out' of the protozoa into the surrounding medium. If this process takes place in the rumen then this would not only recycle amino acids for use in bacterial growth but also provide more amino acids for bacterial deamination, and thus tend to increase the ruminal ammonia concentrations.…”
Section: Y K U R I H a R A J M Eadie P N Hobson And S 0 Mannmentioning
confidence: 99%
“…differed from the Entodinium spp. studied previously (Coleman, 1964(Coleman, ,1972, in that they took up bacteria much less readily on a weight basis. Assuming that the protozoa were cylindrical, the average volumes of an Ento.…”
mentioning
confidence: 99%
“…Approximately 30-40% of the microbial cells were estimated to be degraded in the rumen in these studies. Lysis of micro-organisms (Jarvis, 1968) may be a result of bacteriophage action (Adams, Gazaway, Brailsford, Hartman & Jacobson, 1966 ;Hoogenraad, Hird, Holmes & Millis, 1967), predation of bacteria by protozoa (Coleman, 1964) or death of bacteria from other causes (Hungate, 1966).…”
Section: Symposium Proceedings I973mentioning
confidence: 99%